Modeling Tree Diameter Distributions in Arboretum of Forestry and Wildlife University of Uyo: An Evaluation of 8 Statistical Models (Global Journal of Science Frontier Research, 2020)
The diameter distribution of the growing stock is an essential starting point in many forest management planning problems. Eight distribution functions was used to characterize the size classes of Tectona grandis stands in the arboretum of forestry and Wildlife, University of Uyo, Nigeria. The arboretum comprises of different compartment of trees. The data obtained were diameter at breast height (dbh) measurement of all trees in teak compartment. Using Easyfit modeling software, eight distribution functions was fitted to the data and estimates of the parameters were obtained. The results shows the diameter at breast height data with mean 16.83, standard error 1.08, skewness 1.96 while that of excess kurtosis is 4.84 .The performance of the function was evaluated using Kolmogorov-Simirnov test. Gneralized pareto distribution showed the best performance in terms of quality of fit to the diameter data with the lowest value of 0.0969, shape value of 0.93819.
Keywords: arboretum; diameter modeling; distribution function; tectona grandis